2013
DOI: 10.1037/a0032402
|View full text |Cite
|
Sign up to set email alerts
|

Compared with DBA/2J mice, C57BL/6J mice demonstrate greater preference for saccharin and less avoidance of a cocaine-paired saccharin cue.

Abstract: Rats avoid intake of a saccharin cue when paired with a drug of abuse. While this is true for most subjects, the degree of avoidance of the drug-paired cue depends upon many factors including an individual rat’s preference for rewards. That said, the direction of this effect is complex. For example, reward-preferring Lewis rats exhibit greater cocaine-induced avoidance of a saccharin cue relative to Fischer 344 rats; while reward-preferring mice that over express ΔFosB (NSE-tTA x TetOp-ΔFosB) exhibit less avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
(159 reference statements)
1
12
0
Order By: Relevance
“…The data in the current manuscript demonstrate that ceftriaxone delays acquisition of cocaine-induced suppression in C57BL/6J mice (Figure 2). Published literature of suppression in mice (e.g., Freet et al , 2013, Freet et al , 2014, Freet et al , 2009) demonstrates that saline controls and drug groups start with similar saccharin intake on Trial 1. This makes sense, of course, given that drug (or saline) has yet to be experienced on that trial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data in the current manuscript demonstrate that ceftriaxone delays acquisition of cocaine-induced suppression in C57BL/6J mice (Figure 2). Published literature of suppression in mice (e.g., Freet et al , 2013, Freet et al , 2014, Freet et al , 2009) demonstrates that saline controls and drug groups start with similar saccharin intake on Trial 1. This makes sense, of course, given that drug (or saline) has yet to be experienced on that trial.…”
Section: Discussionmentioning
confidence: 97%
“…injection of either saline (n=15/cell) or 30 mg/kg cocaine (n=15/cell). The 30 mg/kg cocaine dose was used in the current study as published data (Freet et al , 2013) indicates that, in C57BL/6J mice at least, it is the minimum dose required for significant suppression of saccharin intake (i.e., 10 and 20 mg/kg are ineffective in this strain). Taste-drug pairings occurred in the morning for 5 trials (Trials 1–5).…”
Section: Methodsmentioning
confidence: 99%
“…The devaluation of alternative rewards observed in addiction can be modeled in rodents when presentation of a saccharin cue elicits anticipation of the availability of a drug of abuse [20, 28, 29]. In this paradigm, saccharin-saline controls continue to consume saccharin over trials, while rats and mice that have had the saccharin cue paired with a drug of abuse (e.g., cocaine or morphine) avoid intake of the same saccharin cue [20, 23]. It is believed that rodents may initially avoid intake of a saccharin cue, at least in part, because they are anticipating the availability of the highly preferred drug of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have found that animal models of general reward sensitivity (i.e., increased preference not only for drugs of abuse but for natural rewards as well) exhibit an opposite profile (i.e., lesser suppression of intake of the drug-paired taste cue). This is the case for C57BL/6J mice vs. DBA/2J mice [23] and for NSE-tTA × TetOp-ΔFosB mice, a transgenic mouse strain with inducible elevations of the transcription factor ΔFosB [38]. Finally, female Sprague- Dawley rats are known to take more drug and to work harder for drug than males [3941], but when access to cocaine is preceded by brief access to a sweet, female Sprague-Dawley rats ingest more of the saccharin cue and take less drug than their male counterparts [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation